Icts in teaching Spanish to children with hearing disability - Carrillo Salinas, Argenis Maritza; Garcés Amorocho, Mayra Alejandra; Mantilla, Laura Paola (Rastros Rostros, 2012)
This is a research paper that stems from the macro-research “Interaction between icts and bilingual teaching as a functional learning alternative” developed from the second semester of 2010 to the first semester of 2012. The paper presents different processes and methodologies that can be applied for teaching Spanish to children with hearing disability, the study was made with children from first grade at the Escuela Normal Superior de Bucaramanga, the children were chosen during the first semester of 2010. For the development of the research we designed a platform on Moodle. In said platform students can participate in different assignments through which they analyze and interact with the Spanish language. The purpose of this application is to facilitate an adequate promotion of integral development for children with hearing disability, thus giving teachers an auxiliary tool for their daily activities.
Keywords: application; learning; hearing impairmen; interaction; icts